Clinical evolution of patients hospitalized due to the first episode of Acute Coronary Syndrome (Revista Latino-Americana de Enfermagem, 2012)
AIM: to assess the clinical evolution of patients hospitalized due to the first episode of Acute Coronary Syndrome (ACS) according to its clinical manifestation. METHODS: data were collected from 234 patients, hospitalized between May 2006 and July 2009 due to the first episode of an ACS, by consulting their medical records. RESULTS: 234 patients were hospitalized, 140 (59.8%) due to Acute Myocardial Infarction (AMI). In the group with AMI, 19.3% presented complications, against 12.8% in the group with Unstable Angina (UA) (p=0.19). Angioplasty levels were higher among patients with AMI than with UA (p=0.02) and coronary artery bypass graft surgery was more frequent among UA patients (p=0.03). The majority (227; 97%) survived after the coronary event. Among the seven patients who died during the hospitalization, four had AMI (2.9%) and three UA (3.2%). CONCLUSIONS: A larger number of complications were found among infarction victims and the accomplishment of coronary artery bypass graft surgery differed between the groups.